Pengaruh Penghargaan Finansial, Lingkungan Keluarga dan Nilai Intrinsik Pekerjaan Terhadap Minat Mahasiswa Akuntansi Untuk Berkarier Menjadi Akuntan Publik - Ni Komang Sugiantini; Ni Ketut Muliati (UNHI Press, 2023)
Accounting students have a great opportunity to have a career as a public accountant, because those who can follow the professional education of public accounting are someone who has a minimum education of bachelor 1 (S-1), diploma IV or equivalent. A public accountant is an accountant who has obtained permission from the Minister of Finance to provide services, both in the form of attestation services and non-attestation services. Having a good and promising career is the hope and dream that every student wants. This study aims to determine the effect of Financial Rewards, Family Environment and Work Intrinsic Values ??on the Interests of Accounting Students for a career as a Public Accountant. The population in this study were students of the Private University, Accounting Study Program in Denpasar who had entered the 7th semester and above with a total of 2,326 students. The number of samples in this study were 100 respondents who had been determined by the purposive sampling method using the Slovin formula. The research method uses multiple linear regression analysis techniques.The results of this study indicate that Financial Rewards, Family Environment and Work Intrinsic Values ??have a positive and significant effect on the Interest of Accounting Students for a career as Public Accountants. The results of this study can be used as a basis in increasing the interest of accounting students to have a career as a public accountant by providing a deeper understanding and training related to public accounting. In the future, students can improve their ability and understanding of accounting in order to have a career as a public accountant.